Modelling and Analysis of Distributed Program Execution in BETA Using Coloured Petri Nets - Jørgensen, Jens Bæk; Mortensen, Kjeld Høyer (DAIMI Report Series, 1997)
Recently, abstractions supporting distributed program execution in the object-oriented language BETA have been designed. A BETA object on one computer may invoke a remote object, i.e., an object hosted by another computer. In this project, the formalism of Coloured Petri Nets (CP-nets or CPN) is used to describe and analyse the protocol for remote object invocation. In the first place, we build a model in order to describe, understand, and improve the protocol. Remote object invocation in BETA is modelled on the level of threads (lightweight processes) with emphasis on the competition for access to critical regions and shared resources. Secondly, the model is analysed. It is formally proved that it has a set of desirable properties, e.g., absence of dead markings. Topics: Systemdesign and verfication using nets; higher-level nets models; computer tools for nets; experience with using nets, case studies; application of nets to protocols.